Effects of Ammonia‐Induced Surface Modification of Cu(In, Ga)Se2 on High‐Efficiency Zn(O, S)‐Based Cu(In, Ga)Se2 Solar Cells. Issue 2 (21st December 2018) - Li, Jianmin; Ma, Yaping; Chen, Guilin; Gong, Junbo; Wang, Xiaomin; Kong, Yifan; Ma, Xuhang; Wang, Kedong; Li, Weimin; Yang, Chunlei; Xiao, Xudong
Abstract : Post‐treatment of Cu(In, Ga)Se2 (CIGS) surfaces, as an efficient way to improve the performance of CIGS solar cells, has received increasing attention in recent years. To alleviate the limitations of the as‐grown CIGS thin films, such as oxidation, Na accumulation, and microstructure of CIGS surface, ammonia (NH3 ) etching solution was introduced to post‐treat the CIGS surface to improve its quality in this study. To investigate the mechanisms of NH3 etching effects on the CIGS surfaces and the resulted devices, a series of NH3 solution treatments, of different concentrations, on CIGS films is carried out and the resulted surfaces and devices are carefully examined. It is demonstrated that proper concentration of NH3 solution could not only result in a new microstructure between CIGS and Zn(O, S) thin films but also improve the performance of the Zn(O, S) based CIGS solar cells, especially in terms of the device fill factor. As a result, a Zn(O, S) based CIGS solar cell with a conversion efficiency of over 20% is obtained with application of NH3 treatment together with MgF2 anti‐reflective coating. Furthermore, it is found that NH3 treatment could effectively reduce the undesired light soaking effect, which often appears in the Zn(O, S) based CIGS solar cells. Abstract : An ammonia post ‐treatment process is introduced to improve Zn(O, S)‐based CIGS solar cells in this study. Proper concentration of NH3 solution can not only result in a new microstructure between CIGS and Zn(O, S) thin films but also improve the performance of the Zn(O, S)‐based CIGS solar cells, especially for the fill factor (FF).